PENGGUNAAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENGATASI KURANGNYA PERCAYA DIRI SISWA PADA PEMBELAJARAN IPA DI SD - imat Laelasari (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This study was motivated by the limited research on the impact of the role playing learning model on students’ self-confidence, despite its significant effect on learning effectiveness, especially in science subjects. The purpose of this study was to analyze the effectiveness of the role playing method in fostering students’ self-confidence at MI Nurkholis PA. This research employed a qualitative approach with a case study design, involving 10 fifth-grade students selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and analyzed using thematic analysis. The results show that implementing role playing increased students’ courage to speak, active participation, and confidence expression during learning. These findings align with the theory of emotional engagement in learning and highlight the importance of role playing in developing students' affective domains. The main conclusion of this study is that the role playing model is effective in enhancing students’ self-confidence in science learning. The implications include theoretical enrichment in active role-based learning and practical recommendations for teachers to implement this method more broadly in elementary education. This study also opens opportunities for further research on its long-term impacts.